The Impact of Green Bond and Green Budget Tagging on Sustainable Development Moderated by Regulatory Quality: Evidence from Indonesia - Siska, Elmira; Irawan, Rini Larasati; Lestari, Tri; Rahayu, Sri; Alfita, Alya Kanaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The challenges of climate change, environmental decline, and growing pressure on natural resources are pushing both public and private financing systems to shift toward more sustainable and eco-friendly activities. The objective of this study is to examine whether Green Bond issuance, Green Budget Tagging, and Regulatory Quality significantly influence Sustainable Development and whether Regulatory Quality strengthens the relationship between Green Bond, Green Budget Tagging, and Sustainable Development. The research was conducted in Indonesia by using time series data covering period 2018-2023. Data were analyzed using multiple linear regression with moderation testing through SPSS 25. To ensure that the data used in the regression model meet the BLUE (Best Linear Unbiased Estimator) criteria, a series of classical assumption tests were conducted, including the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results show that Green Bond has a significant positive effect on Sustainable Development (sig. 0.000<0.05), while Green Budget Tagging has not shown strong positive impact on Sustainable Development (sig.0.344>0.05). Regulatory Quality has a significant positive effect on Sustainable Development (sig. 0.000<0.05). Simultaneous testing reveals that both variables (Green Bond and Green Budget Tagging) together contribute significantly to Sustainable Development (sig. 0.000<0.05). Regulatory Quality significantly moderates the relationship between Green bond and Sustainable Development (sig. 0.000<0.05). It also significantly moderates the relationship Green Budget Tagging and Sustainable Development (sig. 0.023<0.05). Moreover, the inclusion of Regulatory Quality as a moderating variable increases the adjusted R² value from 0.847 to 0.865, indicating that regulatory quality strengthens the explanatory power of the model. These findings emphasize that the combination of green financing instruments and strong regulatory frameworks plays a crucial role in accelerating Indonesia’s sustainable development agenda.